A tale of two bleeds—an uncommon manifestation in neurofibromatosis-1. (26th February 2019) - Elamurugan, Elamaran; Ram, Duvuru
Abstract: Neurofibromatosis type 1 vasculopathy is a well-documented entity in the literature, but a rupture of the thyrocervical artery aneurysm is very rare and only 2 cases have been reported to date. Our patient presented with a right-sided hemiparesis and deviation of the angle of the mouth to the left. He was diagnosed to have hypertensive bleed in the left capsulo-ganglionic area. He then developed a sudden onset of left-sided neck swelling 8 h following admission, which was due to a ruptured thyrocervical artery aneurysm. To the best of our knowledge, our case is the first case in literature to have presented with simultaneous intracerebral bleed and a thyrocervical artery aneurysm rupture.